Rainbow Washing in Human Resource Management: A Systematic Literature Review of Diversity Rhetoric and Authentic Inclusion - Sain, Zohaib Hassan; Rahimah, Anni (Darul Yasin Al Sys, 2025)
This study presents a systematic literature review (SLR) on the phenomenon of